THE SOAKING EFFECT ON DIFFERENT HYDROCLORIDE ACID LEVEL AND SOAKING TIME ON PH, SWELLING PERCENTAGE AND COLLAGEN YIELD OF CHICKEN SHANK BONE - Puspitasari, D.A.P.; Bintoro, V.P.; Setiani, B.E. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
Collagen is the main ingredient in the gelatin manufacture. The purpose of the study was todetermine the pH value, the swelling percentage and collagen yield of chicken shank bones which weresoaked by different HCl concentration and soaking time. The pH value and swelling percentage ofchicken shank bones are indicator that determines amount of collagen yield. The research design usedwas factorial completely randomized design (CRD). Factor A was a concentration of HCl (2%, 3.5% and5%) and factor B was a soaking time (24, 36 and 48 hours) without replication (profile). The resultshows that the the increase of HCl concentration and soaking time affected on the decreasing of pHvalue profile (0.17-0.85), swelling percentage profile (80.25-97.49%) and also collagen yield (1.80-10.02%). The lowest collagen yield of chicken shank bones was suspected caused by the used of Hcl.The highest result of the study was using 2% of HCl concentration for 24 hours. The best result wasfound in the use of 2% HCl and was soaked for 24 hours. Based on those result, the collagen of chickenshank bones was recommended as a main ingredient for gelatin manufacture.